2017
DOI: 10.1186/s13287-017-0472-y
|View full text |Cite
|
Sign up to set email alerts
|

Intramuscular injection of human umbilical cord-derived mesenchymal stem cells improves cardiac function in dilated cardiomyopathy rats

Abstract: BackgroundStem cells provide a promising candidate for the treatment of the fatal pediatric dilated cardiomyopathy (DCM). This study aimed to investigate the effects of intramuscular injection of human umbilical cord-derived mesenchymal stem cells (hUCMSCs) on the cardiac function of a DCM rat model.MethodsA DCM model was established by intraperitoneal injections of doxorubicin in Sprague-Dawley rats. hUCMSCs at different concentrations or cultured medium were injected via limb skeletal muscles, with blank med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 21 publications
(27 reference statements)
1
31
0
Order By: Relevance
“…When hMSCs are IMtransplanted in immunocompetent animals, a short dwell time of 4-8 days has been reported by Prather et al [22], Francki et al [23], and Hamidian Jahromi et al [38]. Exceptions are the studies by Mao et al [36] and Shabbir et al [34] who reported therapeutic effects for 4 weeks that may infer survival of IM-transplanted hWJ-MSC or pBMMSCs in immunocompetent SD-rats and TO2 hamsters respectively, although more probably reflect the "hit-and-run" mechanism by which MSCs are considered to have their effects [55]. On the contrary, some of the studies that have IM-transplanted MSCs in genetically immunocompromised animal models have reported significant dwell times of 3-24 weeks in injured muscle [22,24,56], 4-16 weeks in intact skeletal muscle of animals with systemic disease [37,39], and 4-32 weeks in intact healthy animals [5,33,[57][58][59].…”
Section: Dwell Time Of Im-delivered Mscsmentioning
confidence: 99%
See 2 more Smart Citations
“…When hMSCs are IMtransplanted in immunocompetent animals, a short dwell time of 4-8 days has been reported by Prather et al [22], Francki et al [23], and Hamidian Jahromi et al [38]. Exceptions are the studies by Mao et al [36] and Shabbir et al [34] who reported therapeutic effects for 4 weeks that may infer survival of IM-transplanted hWJ-MSC or pBMMSCs in immunocompetent SD-rats and TO2 hamsters respectively, although more probably reflect the "hit-and-run" mechanism by which MSCs are considered to have their effects [55]. On the contrary, some of the studies that have IM-transplanted MSCs in genetically immunocompromised animal models have reported significant dwell times of 3-24 weeks in injured muscle [22,24,56], 4-16 weeks in intact skeletal muscle of animals with systemic disease [37,39], and 4-32 weeks in intact healthy animals [5,33,[57][58][59].…”
Section: Dwell Time Of Im-delivered Mscsmentioning
confidence: 99%
“…Similarly, Mao et al IM‐delivered human umbilical cord Wharton's jelly MSCs (hWJMSCs) into both fore limb and hind limbs of doxorubicin‐induced SD rats (a model of dilated cardiomyopathy), two injections 2 weeks apart. Improved cardiac function with increased systemic levels of HGF, IGF‐1, LIF, GM‐CSF, and VEGF and cardiac tissue expression level of HGF, VEGF, and IGF‐1 was observed 2 weeks after the second MSC injection . Furthermore, Liu et al, using human soluble tumor necrosis factor receptor (hsTNFR) transduced hBMMSCs demonstrated a prophylactic reduction in joint inflammation in an antibody‐induced/LPS‐challenged murine rheumatoid arthritis (RA) model, although the naïve hBMMSCs showed no effect .…”
Section: Im‐delivered Mscs To Treat Distant and Systemic Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the administration of autologous cardiosphere‐derived cells and human mesenchymal stem cells to an infarcted heart has shown therapeutic efficacy . These cells have been administered to subjects via intracoronary infusion and intramyocardial injection …”
Section: Soft Bioelectronics–assisted Tissue Engineeringmentioning
confidence: 99%
“…However, with the development of stem cell research, the low transplanting rate, tumorigenicity and the ethics of stem cell transplantation have been widely discussed.Our previous studies found that intramuscular injection of hucMSCs improved the cardiac function in Adriamycin-induced DCM rats, while the transplanted hucMSCs were mainly retained in the muscles,meanwhile the levels of HGF,IGF-1,LIF,GM-CSF and VEGF increased in the myocardium and circulation. The results suggested that paracrine mechanisms may contribute to the therapeutic effect of hucMSCs on DCM [4]. Fang et al found that hucMSC-Ex can reduce the scar formation in wound healing by inhibiting the TGF-b1/SAMD2 pathway [5].Other studies have demonstrated that both MSC and MSC-Ex can reduce the SCI-induced A1 astrocytes by inhibiting the nuclear transport of NF Bp65, thus playing an anti-in ammatory and neuroprotective role [6], but the speci c mechanism remains unknown.…”
mentioning
confidence: 92%